Digital Pathways to Success: The Transformative Power of Digitalization and Digital Capabilities on SMEs’ Financial Performance - Ullah, Muhammad Rizwan; Tahir, Safdar Husain; Shahzadi, Hina; Kamran, Hafiz Waqas (iRASD Journal of Economics, 2023)
In the contemporary competitive business milieu, small and medium enterprises (SMEs) have discerned the significance of embracing the digital landscape to cater to the ever-evolving global customer demands, particularly in the aftermath of the COVID-19 pandemic. This research aims to provide valuable insights into how SMEs navigate the complex digital environment by examining the combinations of digitalization and digital capabilities dimensions that contribute to enhancing financial performance. Different dimensions of digitalization and digital capabilities are used as explanatory variables, while financial performance is an outcome. The study specifically focuses on the SME sector in Pakistan. Employing a fuzzy-set qualitative comparative analysis (fsQCA), the investigation uncovers six novel configurations of factors that drive performance in SMEs, with their roles showing variations depending on accompanying elements. The study identifies six specific combinations (configurations) of determinant antecedents that lead to improved financial performance. Interestingly, the findings highlight that achieving high financial performance is not solely contingent on any individual factor but hinges upon their collective inclusion within causal combinations. By expanding the current understanding of how these antecedents synergistically impact financial performance, this study makes a noteworthy contribution to the literature on firm performance. Furthermore, it offers valuable implications for managers, illuminating the specific factor combinations that pave the way for enhanced performance in the context of SMEs.